IN-FLIGHT WEATHER DATA OBTAINING AND EXCHANGE FOR OPERATIVE FLIGHT PATH CORRECTION - Averyanova, Yu. A. (Science-based technologies, 2014)
In this paper the possibility to use operative information from the dynamic sensors - aircrafts for reconstruction of dangerous weather phenomena actual location and distribution is considered. The algorithm of onboard automated system operation that obtains, exchanges, processes meteorological data and make decision-making support is presented. The system automatically selects and uses operative information that is of high importance for particular flight. The given approach serves to develop safe and economical way of operative flight correction. It is necessary to stress that only the simplest situation is considered in this paper when boarders of dangerous meteorological phenomena is reconstructed using the information from two aircrafts. The presented approach can be used as the basical for broad information flow organization and for control in order to provide the effective information provision and decision-making support to aircraft crew. The results are appointed to satisfy the requirements to modern aviation tendencies and can be used as well to improve the meteorological provision of all corresponding services.